Program Pengabdian Lokakarya Komunitas Belajar Program Sekolah Penggerak Kabupaten Seram Bagian Barat: Community Service Workshop Program Learning Community of Program Sekolah Penggerak West Seram Regency - Hamka, Syamsuar; Aswar, Aswar; Umarella, Samad; Anugerah, Muh. Fahmi (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
This program aims to improve the professional competence of educators in West Seram Regency through the formation and management of sustainable and structured learning communities. Activities are carried out through socialization, workshops, and study group activities that include the stages of analysis, planning, implementation, evaluation, and community development. Program participants consist of 12 representative junior high school teachers in the area. The instruments used include training materials, formative assessments, and the use of digital platforms for monitoring and evaluating the process. The results of the implementation showed a significant increase in the pedagogical and professional competence of teachers, strengthening collaborative networks between schools, and understanding of the continuous learning cycle. The learning communities that were formed were able to facilitate the practice of sharing knowledge and experiences, especially in the implementation of the Merdeka Curriculum. Thus, this program contributes to improving the quality of learning that is oriented towards student learning outcomes and encouraging a culture of collaborative learning in the educational unit environment.